Way of living of the transplanted user from the ecosystem perspective: difficulties and adaptive responses (Research, Society and Development, 2020)
To analyze the way of living of the renal transplanted user under ecosystem approach, their difficulties and adaptive responses in this process. Descriptive, exploratory study with qualitative approach, performed with renal transplant users. Data collection occurred through semi-structured interviews, and Minayo Thematic Analysis was used to analyze the data. The adaptive responses analyzed range from sharing experiences in groups, work and family, to feelings such as optimism/faith and positive thinking. In possession of this information it is possible to qualify nursing care, providing these paths that have already been traversed by other users in a similar condition.